Thomas Hobbes : turning point for honor - Johnson, Laurie M. (Lexington Books, 2009)
Laurie Johnson Bagby examines the loss of the appreciation for honor in modern Western society through an examination of the political philosophy of English political philosopher Thomas Hobbes. She finds in Hobbes's thought a "turning point for h.